Pravovoj režim organov, tkanej i kletok čeloveka posle smerti - Halabudenko, Oleg Anatol'evič (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The paper is devoted to the analysis of the legal regime of human organs, tissues, cells and body. The author argues that the rights in respect of these objects belong to a special group of rights sui generis - somatic rights. It is alleged that a special legal regime acts in regard to the objects of these rights. The paper examines the existing national and international legislation on transplantation of human organs, tissues and cells. It is noted that the rights in respect of the objects may be the object of private legal acts causa mortem taking into account the special legal regime established in relation to them. On the basis of national and international legislation the author demonstrates specifics of such acts
Keywords: legal regime of human organs; tissues; cells and body; somatic rights; national and international legislation on human organs transplantation; donation; causa mortem legal act